Implementasi Kebijakan Absensi Biometrik Terhadap Disiplin Dan Kinerja Aparatur Sipil Negara Pada Biro Umum Sekretariat Daerah Provinsi Kalimantan Tengah - Erry Apriyanti; Nicodemus Nicodemus; Milka Milka (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
This research aims to determine the implementation of biometric absence policy and its impact on the discipline and performance of civil state apparatus at the General Bureau of Central Kalimantan Provincial secretariat based on government regulation Number 53 the year 2010 about civil servants ' discipline. This study examined the policy implementation of the researchers using the Model implementation theory of Donald Van Metter and Carl Van Horn's policy (Agustino,2016:133). The Top-Down approach Model in this theory is a performance of a policy implementation that is essentially intentionally done to achieve a high performance implementation of public policy that takes place in a relationship with six Variables that affect the performance of the policy implementation are the size and objectives of policies, resources, the characteristics of implementing agents, attitudes or tendencies (disposition) of executives, communication between organizations and implementing activities and Economic, social and political environment by relying on that policy implementation runs linearly from available political decisions, executor and public policy performance. The type of research used is qualitative descriptive. Data collection techniques use observations, conduct interviews, and documentation, and then data is analyzed by reduction, data presentation and verification. From the results showed that the application of the biometric attendance policy has been performed well this is seen from the improvement of the discipline and performance of ASN which is already meet the hours of entry (morning apple) and hours of office, HR has character Discipline, communication between leaders and subordinates is always established at all times in a level, the working environment shows a conducive atmosphere. The impact of policy implementation of biometrics absent discipline increases and is coupled with improved performance.